Buya Hamka’s Moral Framework in Tafsir Al-Azhar: Strengthening Muslim Students’ Religious Character in the Digital Era - Mukhlis Mukhlis; Martunis Martunis; Muhammad Syahrial Razali Ibrahim (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2026)
This study aims to analyze Buya Hamka’s concept of morality in Tafsir Al-Azhar on Surah Luqman (31:13–19) and its relevance to strengthening students’ religious character in the digital era. Contemporary students face moral degradation, identity confusion, and social vulnerability caused by uncontrolled digital information flows. These conditions highlight the urgency of developing character education grounded in transcendent religious values and ethical awareness. This research employed a qualitative library-based approach by examining Hamka’s interpretation through the Adabi Ijtima’i perspective. Data were analyzed descriptively to identify the educational values and their contextual application in modern learning environments. The findings reveal that Hamka constructs character through vertical morality based on tawhid and hisbah, which foster spiritual awareness, self-control, and moral integrity in digital interactions. Horizontal morality is reflected in ihsan and gratitude toward parents, moral leadership through amar ma’ruf nahi munkar and patience, and social ethics emphasizing humility and respect. These values support responsible communication, critical information filtering, and ethical digital citizenship. This study contributes a moderate and contextual framework for Islamic character education and recommends integrating reflective digital practices into school curricula.